Racial and ethnic economy inequlity: an international perspective - Myers, Samuel L. (ed.); Corrie, Bruce P. (ed.) (New York Peter lang, 2006)
In a world where racial tensions and racial and ethnic inequality seem to be increasing, it is instructive to look back over the decade of the 1990s to examine what academic researchers have had to say about the global nature of race, racism, and racial inequality. Almost every country with a multiethnic population faces these problems. This collection of essays provides an eclectic but accessible mix of readings on perspectives from such countries as Australia, Russia, France, Chile, West Africa, India, and the United States. Emphasis is placed on positive strategies to help reduce or eliminate economic inequality. The implications for the demise of affirmative action programs are also discussed. Pre-dating the United Nation's World Conference on Racism, the readings anticipate many of the recommendations and insights that have now come to be the core of international strategies. This collection will prove valuable to all those concerned with ending racism and achieving racial and ethnic economic equality.
Keywords: Racism-Congresses